The Effects of Transdermal Estradiol and Oral Conjugated Estrogens on Haemostasis Variables - Kroon, Ulla-Beth; Silfverstolpe, G; Tengborn, L (Thrombosis and Haemostasis, 1994)
The effects of oral and transdermal administration of estrogen replacement therapy (ERT) have been fairly well investigated regarding lipoprotein and carbohydrate metabolism, while the effects of different modes of estrogen administration on the haemostatic system have been less well studied.To delineate and compare the effects of perorally administered conjugated estrogens (CE) and transdermally administered estradiol (E2) in doses needed for hormone replacement therapy (HRT) on haemostasis parameters, 23 postmenopausal women were engaged in a study with an open cross-over design. The doses compared (0.625 mg CE and 50 μg E2/24h) are the lowest which, with few exceptions, eliminate climacteric symptoms. Both CE and E2 increased factor VII:C, factor VII:Ag, and the prothrombin fragment1+2. The increase in factor VII:Ag, however, was significantly higher after treatment with CE. These changes were all towards a state of hypercoagulability. Furthermore, CE decreased plasminogen activator inhibitor (PAI) and the thrombin-antithrombin complexes (TAT), as well as antithrombin (ATIII).